Tourist and recreational use of the rivers in Minsk region: profiling types and limiting factors - Shevtsova, Natali S.; Gordeychuk, Oksana N. (Journal of the Belarusian State University. Geography and Geology, 2017)
On the basis of the methodology of the complex tourist and recreational evaluation of natural potential, mathematical statistics methods and mapping methods using GIS technology of MapInfo the natural potential of the 29 rivers of Minsk region is assessed. The results of a complex assessment of the tourist and recreational natural potential of rivers in Minsk region have shown that from 74 areas located on 29 rivers amateur hunting and recreational fishing stable dominate among other profiling types of recreational activities. There are favorable conditions for realization of rowing by boats on 18 areas, and for driving on yachts on 4 areas. Natural potential of rivers for swimming and snorkeling is very limited. River areas which have opportunities for water skiing arenʼt revealed. Typification of 74 river areas of the Minsk region on 3 types of tourist and recreational use has shown that maximum share of this areas is used by limited multifunctional type – 93.2 %, on the second place – by multifunctional type – 4.1 %, and on the third place – by monofunctional type – 2.7 %. In addition, there are no river areas in Minsk region which arenʼt used for water tourism and rest, demonstrating effective use of tourist and recreational natural potential.
Keywords: tourist and recreational natural potential; river areas; tourism and recreation complex assessment; types of tourist-recreational use; targets and standards; profiling types; multifunctional, limited-multifunctional, monofunctional and unsuitable types of tourist and recreational use